Arab Republic of Egypt : 2007 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Arab Republic of Egypt. (IMF Staff Country Reports; Country Report ;, 2007)
This 2007 Article IV Consultation highlights that sustained and bold reforms, prudent macroeconomic management, and a favorable external environment enabled the Egyptian economy to register another year of impressive performance. Growth remained high and has become more broad based, creating record numbers of jobs. Inflation has returned to single digits after spiking during the year through March 2007. Strong growth and rising equity and real estate prices have boosted domestic demand. Exports also rose sharply, along with worker remittances, Suez Canal receipts, and tourism revenues.